A neurocognitive approach to understand the role of familiarity with musical style and individual differences in music-evoked emotions - Heng, Gladys Jiamin (Nanyang Technological University, 2021)
Music is widely used for leisure, relaxation purposes in everyday life and in healthcare settings. While existing behavioral studies have mapped out basic relationships between musical features and emotions, it remains unclear why different individuals have similar or different emotional responses to music. This points towards a need to examine music-listener relationship, which could be examined by discussing underlying psychological mechanisms and considering an individual’s level of familiarity with a musical style on music-evoked emotions. Neuroimaging studies have also increasingly suggested the involvement of a widely distributed network of brain regions in music-evoked emotions, beyond the established indices of emotional processing (e.g., frontal alpha asymmetry). Moreover, the role of individual differences in music-evoked emotions, particularly absorption trait, are often either not systematically examined or considered in conjunction with neuropsychological processes. Therefore, this thesis aims to integrate perspectives from psychological sciences and neurocognitive sciences to clarify and examine individual variation in music-evoked emotions. This is addressed by two experiments. A pilot behavioral experiment (Study 1) was first conducted to develop a suitable selection of music stimuli of a familiar (Japanese animation soundtracks) and unfamiliar musical style (Greek Laïkó music). 74 healthy young adults listened to music from both musical styles, of which Japanese animation soundtracks elicited emotions of Fear, Power and Nostalgia; and Greek Laïkó music elicited emotions of Joyful activation and Nostalgia. Subsequently, another 49 healthy young adults participated in an electrophysiological (EEG) experiment which was designed to further clarify three research questions separately in a series of three sub-studies (Studies 2A, 2B and 2C). Firstly, Study 2A clarified the electrophysiological correlates of music-evoked emotions by adopting a whole-brain approach to systematically examine EEG activity and brain asymmetries of emotional valence and arousal elicited by music selected from Study 1. Results showed neither support for the hypothesized association between emotional valence and frontal alpha asymmetry/frontal midline theta, nor association between emotional arousal and absolute frontal alpha/right parietal activity. Instead, both pleasant and unpleasant music conditions showed left-biased fronto-occipital and right-biased parieto-temporal asymmetries. Next, Study 2B investigated the effects of familiarity with musical style on music-evoked emotions and found that music of the familiar musical style (Japanese animation soundtracks) was felt as significantly more pleasant as compared to the unfamiliar musical style (Greek Laïkó music). However, music of the unfamiliar musical style (Greek Laïkó music) elicited greater theta power in all brain regions (including the midline region), alpha power in the frontal region, and beta power in fronto-temporo-occipital regions as compared to the familiar musical style. This was postulated to reflect the need for greater attentional resources when listening to music of an unfamiliar style. In addition, classification analyses yielded an accuracy rate of 89.39% - 94.49% in distinguishing between both types of musical style. Lastly, Study 2C investigated the role of absorption trait in music-evoked emotions and its association with EEG activity. Results showed that the moderating effect of absorption was only observed in the arousal ratings of music of the unfamiliar musical style. Specifically, individuals with low absorption trait felt that music of the unfamiliar musical style was significantly more passive as compared to individuals with high absorption trait. However, no significant associations between EEG activity and absorption trait were found. Overall, the current thesis highlights the importance in considering the relationship between music and listener (e.g., familiarity with musical style), as well as the characteristics of the listener (e.g., absorption trait), when examining music-evoked emotions. Taken together, results from this thesis provided further insight into how and why music evokes emotion in different individuals. In so doing, it is hoped that improvements could be made to general well-being and current non-pharmacological personalized treatment approaches in healthcare settings.